The use of handgrip strength (HGS) in outpatient care for patients with Alzheimer’s Disease - Souza Tedrus, Gloria Maria de Almeida; dos Santos, Tamires Barbosa Nascimento; Leandro-Merhi, Vania Aparecida (International Journal of Advanced Engineering Research and Science, 2021)
To evaluate the contribution of handgrip strength (HGS) in outpatient care for elderly patients with Alzheimer’s disease (AD). Cross-sectional study, with AD patients, >65 years of age, who underwent cognitive, nutritional and HGS assessment, International Physical Activity Questionnaire (IPAQ-SF) and Disability Assessment in Dementia (DAD). The data were compared to a similar control group (CG) composed of 51 elderly people, with p <0.05. The 43 elderly people with AD exhibited lower HGS scores when compared to the CG (13.4±8.2 vs 17.5±8.0; p=0.008, Mann-Whitney). There was no difference in HGS according to the severity of dementia, cognitive aspects, the IPAQ-SF and in the activities of daily living in the DAD. Higher HGS values were associated with males and younger age. There was a correlation with some anthropometric indicators. HGS was significantly lower in elderly people with AD. In Alzheimer's disease, higher HGS values were associated with males, younger age and some anthropometric indicators